(untitled) (Semiárida, 2020)
Volumes of small irregular bodies were determined through the movement al a mas of watter. Two different instruments were selected according two sizes of bodies to be analyzed. From the statistical analysis we have done, it is made evident that the metodology used in both cases is satisfactory.